Effect of the number of Cyperus rotundus and medium height on the performance of batch-constructed wetland in treating aquaculture effluent - Imron, Muhammad Fauzul; Hestianingsi, Wa Ode Ayu; Putranto, Trisnadi Widyaleksono Catur; Citrasari, Nita; Abdullah, Siti Rozaimah Sheikh; Hasan, Hassimi Abu; Kurniawan, Setyo Budi (Chemosphere, 2024)
Increasing aquaculture cultivation produces large quantities of wastewater. If not handled properly, it can have negative impacts on the environment. Constructed wetlands (CWs) are one of the phytoremediation methods that can be applied to treat aquaculture effluent. This research was aimed at determining the performance of Cyperus rotundus in removing COD, BOD, TSS, turbidity, ammonia, nitrate, nitrite, and phosphate from the batch CW system. Treatment was carried out for 30 days with variations in the number of plants (10, 15, and 20) and variations in media height (10, 12, and 14 cm). The result showed that aquaculture effluent contains high levels of organic compounds and nutrients, and C. rotundus can grow and thrive in 100% of aquaculture effluent. Besides that, the use of C. rotundus in CWs with the effect of numbers of plants and media height showed performance of COD, BOD, TSS, turbidity, ammonia, nitrate, nitrite, and phosphate with 70, 79, 90, 96, 64, 82, 92, and 48% of removal efficacy, respectively. There was no negative impact observed on C. rotundus growth after exposure to aquaculture effluent, as indicated by the increase in wet weight, dry weight, and growth rate when compared to the control. Thus, adding aquaculture effluent to CWs planted with C. rotundus supports the growth and development of plants while also performing phytoremediation.
Keywords: vodní hospodářství; biodegradace; Environmental pollution; Waste Disposal, Fluid; Ammonia; Wetlands; Cyperus; fosfáty; dusičnany; Phosphates; Plants; Phytotechnology; Sustainable treatment; amoniak; Aquaculture; Biodegradation, Environmental; Nitrites; odpad tekutý - odstraňování; mokřady; rostliny; dusitany; Nitrates